Perancangan PLTS Atap di Gedung Lecture Building Universitas Udayana - Sihombing, Jupael; Sukerayasa, I Wayan; Setiawan, I Nyoman; Janardana, I Gusti Ngurah; Budiastra, I Nyoman; Suartika, I Made (Universitas Pahlawan Tuanku Tambusai, 2025)
The growing demand for electricity in the Province of Bali is still largely dominated by the use of fossil fuels and coal. This reliance on conventional energy sources contributes to carbon dioxide (CO₂) emissions and greenhouse gases, which in the long term have a negative impact on the environment. To reduce this dependency, the utilization of renewable energy sources such as Solar Power Plants (PLTS) offers an effective and environmentally friendly solution. The Lecture Building at Udayana University was selected as the study object due to its relatively high electricity consumption. The PLTS system design for this building was based on the available roof area, utilizing all four roof sides. Each side is equipped with 32 solar modules rated at 670 Wp per unit, one inverter with a capacity of 25 kW, and 16 battery units each with a capacity of 200 Ah. The system design was simulated using PVSyst software, and with a total installed capacity of 85.76 kWp, the system is capable of generating approximately 515.8 kWh of electricity per day.